2016
DOI: 10.1097/igc.0000000000000672
|View full text |Cite
|
Sign up to set email alerts
|

Combined Immunoscore of CD103 and CD3 Identifies Long-Term Survivors in High-Grade Serous Ovarian Cancer

Abstract: These results suggest that combined assessment of CD103 and CD3 counts improves the prognostic value of TIL counts in HGSC and might identify patients with early relapse or long-term survival based on the type and extent of the immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 31 publications
4
62
1
2
Order By: Relevance
“…First, we confirmed the recent reports on the prognostic benefit of CD103+ TIL in HGSC [7,11] in an independent cohort of advanced-stage HGSC patients treated with either primary surgery and adjuvant chemotherapy (PS; n=84), or neo-adjuvant chemotherapy followed by interval surgery (NACT; n=102) [12]. CD3+, CD8+ and CD103+ TIL were present in tumors from most patients and the distribution of CD3+ and CD8+ TIL in tumor epithelium and stroma was similar (Figure 1A).…”
Section: Resultssupporting
confidence: 89%
“…First, we confirmed the recent reports on the prognostic benefit of CD103+ TIL in HGSC [7,11] in an independent cohort of advanced-stage HGSC patients treated with either primary surgery and adjuvant chemotherapy (PS; n=84), or neo-adjuvant chemotherapy followed by interval surgery (NACT; n=102) [12]. CD3+, CD8+ and CD103+ TIL were present in tumors from most patients and the distribution of CD3+ and CD8+ TIL in tumor epithelium and stroma was similar (Figure 1A).…”
Section: Resultssupporting
confidence: 89%
“…Webb et al have demonstrated that the integrin CD103, which binds to E-cadherin expressed by epithelial cells, is highly expressed by intra-epithelial effector T cells in ovarian carcinoma, and suggested that it is these CD103 + T cells that contribute to the improved prognosis seen with high levels of TILs [201]. Similarly, Bosmuller et al found CD103 added prognostic value to conventional T cell markers in the assessment of TILs in ovarian carcinoma [202]. However, two studies have reported important prognostic value of TILs in the stromal compartment, similar to that seen in the epithelial compartment [203,204].…”
Section: Tils In Gynecological Carcinomasmentioning
confidence: 99%
“…This cohort has been published previously. 18 Age, stage, and response rates to platinum-based chemotherapy are within the expected range. As expected, platinum sensitivity was the strongest predictor of prognosis.…”
Section: Immunohistochemical Findingsmentioning
confidence: 93%
“…The construction of the TMAs was performed as recently published. 17,18 Each case was represented by six cores, three from each side in the case of bilateral tumors, and 3 each from 2 different areas in unilateral tumors, with 0.6 mm diameter, punched with a semiautomatic tissue array instrument (Beecher Instruments Sun Prairie, WI). Cores with 1.0 mm diameter were used for low-grade serous carcinoma (LGSOCs) and serous borderline tumors.…”
Section: Tma and Immunohistochemistrymentioning
confidence: 99%